Deteksi Dini Tumbuh Kembang (Ddtk) Anak Usia 4-6 Tahun Dengan Kuesioner Pra Skrining Pertumbuhan (Kpsp) - Permatasari, Dian Intan; Nafi'ah, Nafi'ah (Politeknik Unggulan Kalimantan, 2024)
Growth and development is a process that occurs continuously from conception and continues into adulthood. In the process of child development, early detection is needed to identify early problems from the normality of child development. The purpose of this study is to find out the description of the growth and development of early childhood aged 4-6 years. The research method used was descriptive qualitative which was conducted on 40 children aged 4-6 years, to determine growth using body mass index (BMI) measurements and to determine development using a developmental pre-screening questionnaire (KPSP). Based on BMI measurements, the highest results were found in the normal category of 25 people with a percentage of 62.5%. Meanwhile, based on KPSP, according to the age of 28 people with a percentage of 70%. The most based on age, namely 28 people aged 5 years with a percentage of 70%, and the most based on gender, namely 21 men with a percentage of 52.5%.